Social innovation in the perspective of a poststructuralist theory of practice: Critique of the parallel use of praxeological and actor-theoretical paradigm - Brandauer, Roland (Momentum Quarterly, 2020)
The Research Group of Dortmund, represented by well-known German sociologists like Howaldt, Jacobsen, Kopp and Schwarz, is pursuing the promising project of substantiating social innovation as a poststructuralist version of practice theory. In order to establish social innovation as a dominant ´driver´ of social change towards technological and economic innovation, these scientists remain, on the other hand, faithful to the actor-theoretical paradigm of an intentional subject. In a theory comparison the two approaches are proving to be strongly divergent with regard to the central concepts of subject and intention which are of major importance in defining social innovation. This study puts, forward the thesis that, although in the conception of a multi-paradigmatic science there can exist for a certain period contradictory paradigms in a parallel way, the use of contradictory paradigms within a research program is untenable at logical, content and epistemological levels.